A contribuição de Marcuse para a questão da disciplina - Schmidt, Dagoberto Augusto de Toledo (2003)
This work intends to demonstrate the contribution of Marcuse´s work to the comprehension of the phenomen of indiscipline in the classroom, its origin and its development. We will utilize the scale notion , present in the work of Luiz Roberto Salinas Fortes, in which is analised the philosofical work of J.-J. Rousseau, looking for to reduce the possible contradictions in his work. The utilization of this notion tries to demonstrate that, in accordance with Freud´s thought as read by Marcuse, it is possible to enlight the question of the relation between teacher´s work and phenomen of school indiscipline, in a new perspective. We will see that, understood the question of a scission of knowledge and its genesis, from a starting point of social labour division, such a phenomenon borns from a lack of sense, originated as a consequence of the development of Modern Philosophy. Pointed the causes we will show that the solution of the problem pass through the attempt of reconstruction of this lost sense, from the ampliation of the concept of reason.